ANALISIS PENGARUH PENDAPATAN, GAYA HIDUP, DAN KEBUTUHAN TERHADAP KEPUTUSAN MENGGUNAKAN KARTU KREDIT BCA DI SURABAYA - Polisoa, Mila Utary; Andayani, Sri; Maduwinarti, Ayun (Jurnal Dinamika Administrasi Bisnis, 2015)
This thesis is aimed to determine the effect of income, lifestyle, and life necessity toward. Source of the data in this study is come from 75 consumers of BCA-Credit Card in Surabaya. Data analysis technique was multiple linear regression with SPSS program for Windows. The results showed that income has tstatistic of 3.894 with significant level by 0.000, so variabel of income (X1) significantly influences the decision to use BCA-Credit Card in Surabaya. Lifestyle (X2) has tstatistic of 2.963 with significant level by 0.004, so variable of Lifestyle (X2) significantly influence the decision to use BCA-Credit Card in Surabaya. Life necessity (X3) has tstatistic of 3.470 with significant level by 0.001, so variable of Life necessity (X3) significantly influences the decision to use BCA-Credit Card in Surabaya. Finally, the variable of income is variable with the largest standardized coefficients among other variables so that the income variable is the dominant variable that influence on the decision to use BCA-Credit Card in Surabaya.Keywords: income, lifestyle, life necessity, decision, credit card.